The evolution of ecological facilitation within mixed-species biofilms in the mouse gastrointestinal tract. Issue 11 (November 2018) - Lin, Xiaoxi; Wang, Tuo; Stothard, Paul; Corander, Jukka; Wang, Jun; Baines, John F.; Knowles, Sarah; Baltrūnaitė, Laima; Tasseva, Guergana; Schmaltz, Robert; Tollenaar, Stephanie; Cody, Liz; et al.
Abstract The eco-evolutionary interactions among members of the vertebrate gut microbiota that ultimately result in host-specific communities are poorly understood. Here we show thatLactobacillus reuteri coexists with  species that belong to theLactobacillus johnsonii cluster (L. johnsonii, L. gasseri, andL taiwanensis ) in a taxonomically wide range of rodents, suggesting cohabitation over evolutionary times. The two dominantLactobacillus species found in wild mice establish a commensalistic relationship in gastric biofilms when introduced together into germ-free mice in whichL. reuteri facilitates colonization ofL. taiwanensis . Genomic analysis revealed allopatric diversification in strains of both species that originated from geographically separated locations (Scotland and France). Allopatry of the strains resulted in reduced formation of mixed biofilmsin vitro, indicating that interspecies interactions in gastricLactobacillus -biofilms are the result of an adaptive evolutionary process that occurred in a biogeographical context. In summary, these findings suggest that members within the vertebrate gut microbiota can evolve inter-dependencies through ecological facilitation, which could represent one mechanism by which host-specific bacterial communities assemble across vertebrate species and an explanation for their spatial and biogeographic patterns.